'Perezhivanie' in Group Settings: A Cultural-Historical Reading of Emotion Regulation. Issue 3 (September 2013) - Fleer, Marilyn; Hammer, Marie
THERE IS AN OVERWHELMING AMOUNT of research on emotion regulation (e.g. Barblett & Maloney, 2010; Koole, 2010). Much of this work has centred on experimental studies rather than group settings such as childcare centres and kindergartens. In drawing upon cultural-historical concepts, this paper presents a theoretical discussion on how fairytales help children to collectively develop emotion regulation. We specifically explore emotions and cognition during the telling, re-telling, and role-playing of fairytales. It is argued that fairytales can act as a pedagogical framework for helping children become more conscious of emotions as they role play. Cultural-historical theory is used to give a new perspective on both fairytales and emotion regulation.